The premodern condition (2008)
After the events of September 11, premodern nations have been questioned by “humanity,” and the political and judicial scope of “minorities” accounts linked to ethnic identities, land and re ligion are looked at with distrust. The task of civilization acquires, once again, the features of a crusade to save Christianity as well as the promises of liberalism and the market economy throughout the world. The effects of this crusade on democratic restrictions depend on the consensus war achieves